Study on the adsorption of zinc from waste ipa by using granular activated carbon - Wan Zulaisa Amira, Wan Jusoh (2012)
The spent Isopropyl Alcohol(IPA)is a schedule waste from electrical and electronic manufacturing industries which is also abundance in our country.The IPA waste containing high concentration of electronic waste mainly comprises a few heavy metals whichhas the potential of purifying and reusingthe waste by removingheavy metals from it.The aim of the study was tofind optimum adsorption parameter for Zink removal from the spentIPAby utilizingthegranular activatedcarbon (GAC).Investigation was carried out by studying the influence of the initial solution pH value ranging from 4 to 10, different temperature value ranging from 25 to 35oC and also agitation speed using incubator shaker that operated for 50,100 and 150rpm in thebatch reactor.Theadsorption capacityon the molar basis of heavy metal from spent IPA was analyzed by using Atomic Adsorption Spectrometer (AAS).The heavy metal Zink(Zn)were able to be stripped from the IPA.The maximum and most significant of zinc removal percentage is89.7% with is from 1.4621mg/L to 0.1506 mg/L at parameter of 30.8oC,98rpm and pH4.The colour of waste samples were able to change from grey to colourless and strong odor of waste IPA became less at the end of the experiment.